2012
DOI: 10.1242/dev.071035
|View full text |Cite
|
Sign up to set email alerts
|

Rankl-induced osteoclastogenesis leads to loss of mineralization in a medaka osteoporosis model

Abstract: SUMMARYOsteoclasts are macrophage-related bone resorbing cells of hematopoietic origin. Factors that regulate osteoclastogenesis are of great interest for investigating the pathology and treatment of bone diseases such as osteoporosis. In mammals, receptor activator of NF-B ligand (Rankl) is a regulator of osteoclast formation and activation: its misexpression causes osteoclast stimulation and osteoporotic bone loss. Here, we report an osteoporotic phenotype that is induced by overexpression of Rankl in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(128 citation statements)
references
References 45 publications
4
117
0
7
Order By: Relevance
“…In this study, the down-regulation of miR-218 was confirmed during the process of RANKL-induced osteoclastogenesis, in both osteoclast precursors of BMMs and RAW 264.7. Accumulating evidences have proven that RANKL can induce osteoclast formation by various signaling, which will facilitate the development of osteoporosis [22,23]. In our studies, we found that miR-218 overexpression significantly abrogated RANKL-induced cell-cell fusion of TRAP-positive mononuclear pre-osteoclasts to become multinuclear mature osteoclasts, concomitant with the down-regulation of Trap and Cathepsin K levels, both the master regulators of osteoclastogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…In this study, the down-regulation of miR-218 was confirmed during the process of RANKL-induced osteoclastogenesis, in both osteoclast precursors of BMMs and RAW 264.7. Accumulating evidences have proven that RANKL can induce osteoclast formation by various signaling, which will facilitate the development of osteoporosis [22,23]. In our studies, we found that miR-218 overexpression significantly abrogated RANKL-induced cell-cell fusion of TRAP-positive mononuclear pre-osteoclasts to become multinuclear mature osteoclasts, concomitant with the down-regulation of Trap and Cathepsin K levels, both the master regulators of osteoclastogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Microdissection of cartilage was performed according to DeLaurier et al (2010). Imaging was performed according to To et al (2012).…”
Section: Analysis Of Osx Relationships Within Vertebratesmentioning
confidence: 99%
“…58,64,65 Given that signaling proteins like sclerostin and RANKL allow osteocytes to act as significant regulators of osteoblast and osteoclast activity and the interplay between them, controlling the rate and extent of bone formation and resorption, it is appealing to ask what control mechanisms exist in bone without osteocytes, and which mechanisms may be conserved between fishes and other vertebrates. Although these questions are largely unaddressed in fishes (but see To et al 66 ), it is clear that, in general, the regulatory measures attributed to osteocytes are not simply absent in acellular bone. Moreover, acellular bone does not appear as mammalian bone with the osteocytes simply removed or dead, a manipulation that alters SCL and RANKL levels and can have drastic effects on the balance between bone gain and loss.…”
Section: Modeling: Evidence For and Implications In Acellular Bonementioning
confidence: 99%
“…18 Clearly, although osteocytes are lacking, bone production and removal do not run rampant in acellular fish bone, although RANKL has recently been shown to exist and have a conserved role in the skeleton of an acellular teleost fish. 66 This suggests alternative regulation factors and/or control pathways, perhaps via osteoblast control of RANKL, although parathyroid hormone (known to promote osteoblast expression of RANKL in mammals) is present in quite different form in fishes, and fishes lack parathyroid glands. 60,67 Determination of the precise triggering and activation machineries involved, the sequence of gene expression in regulation and coordination, and the cells that take part in sensing the need for fish bone modeling can be made by a combination of histological, biochemical and molecular genetics methods.…”
Section: Modeling: Evidence For and Implications In Acellular Bonementioning
confidence: 99%